Study on Percent Recovery of Nitrogen in Incubation with Five BGA (Blue-green algae) Species at Four Temperature and Three Moisture Conditions (Bangladesh Journal of Scientific and Industrial Research, 2007)
Bangladesh J. Sci. Ind. Res. 42(2), 235-238, 2007